Acid-base regulation in the sea urchin Parechinus angulosus during CO₂-induced seawater acidification - Dyer, Alexei (Department of Biological Sciences, 2014)
Ocean acidification is predicted to have adverse effects on the physiologies of marine organisms, particularly those that produce calcified structures. Extracellular homeostasis is considered to be critical to mediating the effects of ocean acidification. Due to their low metabolic rates and weak ability to regulate ion exchange, sea urchins are thought to be particularly weak acid-base regulators. Recent findings showing species-specific capacities for extracellular pH regulation however suggest that species currently exposed to natural CO₂ elevations, such as upwelling events, may have a higher capacity tolerate elevated CO₂. The sea urchin Parechinus angulosus currently experiences natural CO₂ variations within the Benguela upwelling system and is therefore predicted to possess the capacity to compensate moderate acid-base disturbances. Urchins were submitted to control (8.0), intermediate (7.7) and low (7.4) seawater pH treatments for 14 days to investigate the capacity to regulate extracellular acid-base status. Extracellular pH changes induced by exposure to intermediate (pH 7.7) seawater acidification were fully compensated through the accumulation of approximately 2.0 mmol l-1 of bicarbonate. The bicarbonate accumulation was only sufficient to partially compensate extracellular acid-base status during exposure to low (7.4) seawater pH. Results from acute (24 hour) exposure to low (7.4) seawater pH reveal that bicarbonate accumulation, despite being evident within 24 hours, is not sufficient to compensate extracellular pH. This study provides further support that sea urchins exposed to natural CO₂ variability possess a limited capacity to regulate extracellular acid-base disturbances. P.angulosus may therefore already be adapted to deal with a moderate reduction in seawater pH to 7.7, but lacks the iono-regulatory capacity to accumulate sufficient bicarbonate to deal with a reduction of seawater pH to 7.3. Long-term studies are needed to assess the role of acid-base regulation as a mediator of broader physiological tolerance to ocean acidification, and its consequences at the level of the whole organism.